Psychometric Properties of the Competencies Compound Inventory for the Twenty-First Century - Celume, Macarena-Paz; Maoulida, Haïfat (Frontiers in Education, 2022)
The world is evolving rapidly, implying that the jobs of tomorrow, the socio-economic problems, and the technologies we will have to interact with, will no longer exist. For this, a new set of skills and competencies will be necessary and these will allow us to face the 21st century. The "Four-Dimensional Education" model from the Centre of Curriculum Redesign (CCR) developed by Fadel and collaborators (2015) stands out by proposing a framework that organises twelve competencies for the 21st century, defines them in a clear and usable way, and provides levels for action for all education stakeholders. Based on this model a self-reported scale was built in order to assess these competencies. The purpose of this study is to present the psychometric properties of this scale with the objective of measuring this specific set of competencies. The results showed good psychometric properties, presenting a sensitive, reliable and valid scale to measure 21st-century competencies